HUBUNGAN ANTARA FEAR OF MISSING OUT DENGAN KONFORMITAS PADA PENGGUNA INSTAGRAM DI KALANGAN GENERASI Z - Hana Kameliana Romansza; Widya Risnawaty (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Generation Z is a cohort that has grown up alongside rapid technological advancements, making them highly familiar with social media use, particularly Instagram. This platform functions not only as a medium for sharing information but also as a space for constructing self-identity through social interaction and engagement with emerging trends. High levels of Instagram use can lead to the emergence of Fear of Missing Out (FoMO), characterized by anxiety about being left out of others’ social experiences. This condition may contribute to a stronger tendency to conform to social norms or behavioral expectations within online environments.This study aims to examine the relationship between FoMO and conformity among Generation Z Instagram users. The sampling process employed a non-probability purposive sampling technique, involving 403 respondents recruited through an online questionnaire distributed via Google Form. Data analysis revealed a significant positive correlation between FoMO and conformity, with a correlation coefficient of r = 0.453 and p < 0.001 (p < 0.05). These findings indicate that higher levels of FoMO are associated with a greater inclination to engage in conforming behaviors on Instagram. Overall, the results underscore the role of FoMO in increasing conformity tendencies among Generation Z social media users.